New species of black flies (Diptera: Simuliidae) from Nepal - Takaoka, H.; Shrestha, S. (Magnolia Press, 2010)
Ten new species of black flies are described based on larval, pupal and reared adult specimens collected at various localities in Nepal. All new species are assigned to the genus Simulium Latreille and further classified into five subgenera: one (S. suchitrae sp. nov.) in Asiosimulium Takaoka & Choochote, one (S. jomsomense sp. nov.) in Eusimulium Roubaud, three (S. baglungense sp. nov., S. butwalense sp. nov., S. nuwakotense sp. nov.) in Gomphostilbia Enderlein, two (S. lekhaniense sp. nov., S. letense sp. nov.) in Nevermannia Enderlein, and three (S. titarense sp. nov., S. tamorense sp. nov., S. tulshii sp. nov.) in Simulium Latreille s. str. Among these, the first two new species also represnt new records from Nepal of two subgenera, Asiosimulium and Eusimulium, respectively, both of which occur very rarely in the Oriental Region. The previous record from Nepal of S. (G.) gombakense Takaoka & Davies is corrected to that of S. (G.) sachini Takaoka & Henry, recently described from India. The male and mature larva of S. (G.) sachini are also described for the first time. The taxonomic affinities with related known species, if any, are noted for each new species. The keys to all 32 Nepalese species of black flies are provided.